Leverage and investment under a state-owned bank lending environment: Evidence from China - Firth, Michael; Lin, Chen; Wong, Sonia M.L. (Journal of Corporate Finance, 2008)
This study examines the relations between leverage and investment in China's listed firms, where corporate debt is principally provided by state-owned banks. We obtain three major findings. First, there is a negative relation between leverage and investment. Second, the negative relation between leverage and investment is weaker in firms with low growth opportunities and poor operating performance than in firms with high growth opportunities and good operating performance. Third, the negative relation between leverage and investment is weaker in firms with a higher level of state shareholding than in firms with a lower level of state shareholding. Overall, our results are consistent with the hypothesis that the state-owned banks in China impose fewer restrictions on the capital expenditures of low growth and poorly performing firms and also firms with greater state ownership. This creates an overinvestment bias in these firms.